Characterization of Extended-Spectrum Beta-Lactamase-Producing Escherichia coli in Diarrhoeal Faeces from 0 to 5-Year-Old Children Attending Public Hospitals in Franceville, Gabon - Anicet-Clotaire Dikoumba; Pierre Philippe Mbehang Nguema; Leresche Even Doneilly Oyaba Yinda; Romeo Wenceslas Lendamba; Jean Constan Obague Mbeang; Guy Roger Ndong Atome; Christophe Roland Zinga Koumba; Sylvain Godreuil; Richard Onanga (MDPI AG, 2024)
Background: In Gabon, studies on the characterization of extended-spectrum beta-lactamase-producing Escherichia coli in young children with diarrhoea are almost nonexistent. The objective was to evaluate the prevalence of antibiotic resistance to extended-spectrum beta-lactamase-producing Escherichia coli in children at public hospitals in Franceville, Gabon. Methods: Seventy diarrhoea faecal samples were collected from children aged 0-5 years. The culture and isolation of colonies were carried out on MacConkey agar. The colonies were identified using VITEK 2. The determination of the extended-spectrum beta-lactamase's profiles was accomplished using the double disk method. The identification of phylogroups and pathotypes was performed by PCR. Identification of the ESBL genes was performed by sequencing. Results: A total of 26 strains of Escherichia coli (33.0%) were identified from 78 bacterial isolates. Twenty (77.0%) Escherichia coli strains carried extended-spectrum beta-lactamases blaCTX-M-15 and 5.0% carried blaSHV-12 subtypes. Phylogroup D (62.0%) was predominant, followed by B1 (12.0%), B2 (8.0%) and E (4.0%). The bacterial pathogens causing diarrhoea were enterohemorrhagic E. coli (12.0%), typical enteropathogenic Escherichia coli (8.0%), atypical enteropathogenic Escherichia coli (4.0%), Enteroaggregative Escherichia coli (4.0%) and enteroinvasive E. coli (4.0%). Conclusions: This study showed a high prevalence of extended-spectrum beta-lactamase, Escherichia coli of phylogroup D and pathotype enterohemorrhagic Escherichia coli in children under 5 years old in public hospitals in Franceville, most probably due to the misuse or inappropriate consumption of beta-lactams.